2016
DOI: 10.18632/oncotarget.13474
|View full text |Cite
|
Sign up to set email alerts
|

M2 macrophages induce ovarian cancer cell proliferation via a heparin binding epidermal growth factor/matrix metalloproteinase 9 intercellular feedback loop

Abstract: In ovarian cancer, a high ratio of anti-inflammatory M2 to pro-inflammatory M1 macrophages correlates with poor patient prognosis. The mechanisms driving poor tumor outcome as a result of the presence of M2 macrophages in the tumor microenvironment remain unclear and are challenging to study with current techniques. Therefore, in this study we utilized a micro-culture device previously developed by our lab to model concentrated paracrine signaling in order to address our hypothesis that interactions between M2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 51 publications
1
56
0
Order By: Relevance
“…The TME is a supportive and receptive tissue microenvironment undergoing a series of molecular and cellular changes to form metastatic-designated sites, or the fertile soil in preparation for metastatic tumor cell seed colonization, thus supporting tumor settlement in distant organs and promoting tumor metastasis (6)(7)(8). As the most common immune cells in the TME, TAMs infiltrate the TME in OC in large numbers and play an important role in the formation of the OC TME and education of OC cells to develop to become more malignant by secreting various factors, such as IL-6 and IDO (16,18,19,39,40). Indeed, therapeutic methods targeting TAMs have been demonstrated as effective for controlling OC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TME is a supportive and receptive tissue microenvironment undergoing a series of molecular and cellular changes to form metastatic-designated sites, or the fertile soil in preparation for metastatic tumor cell seed colonization, thus supporting tumor settlement in distant organs and promoting tumor metastasis (6)(7)(8). As the most common immune cells in the TME, TAMs infiltrate the TME in OC in large numbers and play an important role in the formation of the OC TME and education of OC cells to develop to become more malignant by secreting various factors, such as IL-6 and IDO (16,18,19,39,40). Indeed, therapeutic methods targeting TAMs have been demonstrated as effective for controlling OC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the microenvironment within tumor tissues, TAMs are also distributed in some special organs and lymph nodes, associated with metastasis to these regions (13,14). TAMs infiltrate into OC tissues in large numbers (15)(16)(17), contributing to the progression of OC (18,19), thus negatively affecting the progression-free survival rates and overall survival rates of these patients (16). However, the precise mechanism of how TAMs contribute to the progression of OC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Tumorassociated macrophages can secrete epidermal growth factor (EGF), which activates epithelial EGFR pathway, and exerts protumorigenic effects on the neoplastic epithelium. 31,32 We first screened EGF and EGFR expression in our co-cultured macrophages and pancreas organoids (WT) by quantitative PCR. EGF was highly expressed in macrophages, but not in epithelial organoids, whereas EGFR was highly expressed in epithelial organoids ( Fig.…”
Section: Macrophages Reduce Epithelial Pedf Via Egf/egfr Pathwaymentioning
confidence: 99%
“…It has been reported that enzymes matrix metalloproteinases 9 (MMP9) and matrix metalloproteinases 3 (MMP3) are involved in the cleavage of pro-HBEGF to form s-HBEGF. 37,38 Interestingly, we also observed that sorafenib could increase both MMP9 and MMP3 protein levels in a transcription-dependent manner (Supplementary information, Fig. S2a, b).…”
Section: Vascular Endothelial Cells Contribute To Sorafenib-induced Hmentioning
confidence: 62%